Efeito de frequências de suplementação no comportamento ingestivo, padrão de deslocamento e ingestão de matéria seca por novilhas de corte - Sichonany, Maria José de Oliveira (2012)
The dry matter intake, ingestive behavior and displacement patterns were evaluated on beef heifers exclusively on pasture or receiving oats grain daily ( frequent ) or from Monday to Friday ( infrequent ) in "Vegetative" and "Reproductive" phenological stages of Alexandergrass (Urochloa plantaginea Link.). The grazing method was continuous with a variable number of animals. The experimental design was completely randomized, in a factorial 3 x 2 arrangement (three supplementation frequency and two phenological stages). Forage intake was estimated using chromium oxide as an indicator of fecal output. Forage intake was greater for heifers exclusively on pasture and daily supplemented (2.91% of body weight (BW)) than for heifers receiving infrequent supplementation (2.00% of BW). Forage intake was greater in "Vegetative" than "Reproductive stage. Changes in supplementation frequency and phenological stages of Alexandergrass caused variation in the use of feeding stations. The grazing time was diminished and the bites were heavier when heifers received daily supplementation. The bite weight and grazing time were similar in phenological stages while the bite rate decreased in the reproductive stage. Changes in supplementation frequency and in phenological stages of alexandergrass modify the feeding behavior and forage intake of beef heifers.